2017
DOI: 10.3389/fpls.2017.01781
|View full text |Cite
|
Sign up to set email alerts
|

Traits Explaining Durum Wheat (Triticum turgidum L. spp. Durum) Yield in Dry Chilean Mediterranean Environments

Abstract: Yield under water stress (YS) is used as the main criterion in the selection of wheat varieties for dry Mediterranean environments. It has been proposed that selection of genotypes using YS assisted by morphological and physiological traits associated with YS is more efficient in selecting high yielding genotypes for dry environments. A study was carried out at the Antumapu Experiment Station of the University of Chile, located in Santiago, Chile (33° 40′S and 70° 38′ W). The objective was to evaluate the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
6
18
0
Order By: Relevance
“…Broad-sense heritability was low to medium, (51.02%), suggesting a sizeable environmental effect on the expression of this trait. In their studies, Graziani et al [2] and González-Ribot et al [25] found a low heritability of 27% for spike number. Similarly, grain and straw yields expressed low broad-sense heritability, high phenotypic and genotypic coefficients of variation, and significant ranges.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Broad-sense heritability was low to medium, (51.02%), suggesting a sizeable environmental effect on the expression of this trait. In their studies, Graziani et al [2] and González-Ribot et al [25] found a low heritability of 27% for spike number. Similarly, grain and straw yields expressed low broad-sense heritability, high phenotypic and genotypic coefficients of variation, and significant ranges.…”
Section: Resultsmentioning
confidence: 92%
“…Based on genotypic coefficient of variation and broad-sense heritability, aboveground biomass appeared to be amenable to improvement, within the set of studied genotypes. González-Ribot et al [25] reported a very low heritability of 9% for aboveground biomass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traits associated with drought tolerance in durum wheat 485 morphological and physiological traits associated with yield under the drought stress is more efficient in selecting high yielding genotypes for dry environments (González-Ribot et al, 2017).…”
mentioning
confidence: 99%